Effects of blocking mGluR5 on primate dorsolateral prefrontal cortical neuronal firing and working memory performance - Yang, Sheng-Tao (Psychopharmacology (Berl), 2020)
RATIONALE: Metabotropic glutamate type 5 receptor (mGluR5) antagonists are under development for treating cognitive disorders such as Fragile X syndrome and Alzheimer’s disease, largely based on success in mouse models, where post-synaptic mGluR5 stimulation weakens synaptic functions in hippocampus. However, human trials of mGluR5 antagonists have yet to be successful. This may be due in part to the differing effects of mGluR5 in hippocampus vs. prefrontal cortex, as mGluR5 are primarily post-synaptic in rodent hippocampus, but are both pre- and post-synaptic in the dorsolateral prefrontal cortical (dlPFC) circuits known to subserve working memory. OBJECTIVES AND METHODS: The current study examined the effects of the selective mGluR5 negative allosteric modulator, MTEP (3-((2-Methyl-1,3-thiazol-4-yl)ethynyl)pyridine hydrochloride), on neuronal firing and working memory performance in aging rhesus monkeys with naturally occurring impairments in neuronal firing and cognitive performance. RESULTS: We found that iontophoresis of MTEP directly onto dlPFC “Delay cells” had an inverted U dose-response, where low doses tended to enhance task-related firing, but higher doses suppressed neuronal firing. Similar effects were seen on cognitive performance following systemic MTEP administration (0.0001–0.1 mg/kg), with MTEP producing erratic dose-response curves. In the subset of monkeys (50%) that showed replicable improvement with MTEP, co-administration with the mGluR5 PAM, CDPPB (3-Cyano-N-(1,3-diphenyl-1H-pyrazol-5-yl)benzamide), blocked MTEP beneficial effects, consistent with mGluR5 actions. CONCLUSIONS: The mixed effects of MTEP on cognitive performance may arise from opposing actions at pre- vs. post-synaptic mGluR5 in dlPFC. These data from monkeys suggest that future clinical trials should include low doses, and identification of potential subgroup responders.